Family interventions for relapse prevention in schizophrenia: a systematic review and network meta-analysis. (March 2022) - Rodolico, Alessandro; Bighelli, Irene; Avanzato, Chiara; Concerto, Carmen; Cutrufelli, Pierfelice; Mineo, Ludovico; Schneider-Thoma, Johannes; Siafis, Spyridon; Signorelli, Maria Salvina; Wu, Hui; Wang, Dongfang; Furukawa, Toshi A; et al.
Summary: Background: Family interventions are efficacious for relapse prevention in schizophrenia. Multiple different models have been developed. We aimed to compare the efficacy, acceptability, and tolerability of family interventions for relapse prevention in schizophrenia. Methods: In this systematic review and network meta-analysis, we searched for randomised controlled trials that investigated family intervention models aimed at preventing relapse in patients with schizophrenia. We searched EMBASE, MEDLINE, PsycINFO, BIOSIS, CENTRAL, ClinicalTrials.gov, and WHO International Clinical Trials Registry Platform up to Jan 20, 2020 and PubMed up to July 15, 2021. We included blinded and open-label randomised controlled trials in which at least 80% of patients had schizophrenia spectrum disorders. We excluded studies in which all patients were acutely ill, had a concurrent medical or psychiatric disorder, or were prodromal or "at risk of psychosis". Study selection and data extraction were done by two independent reviewers. Data were extracted about overall, positive, negative, and depressive symptoms of schizophrenia, quality of life, adherence, overall functioning, family burden, expressed emotion, and discontinuations due to inefficacy. The primary outcome was relapse, measured with operationalised criteria, psychiatric hospital admissions, or clinical judgement. We did a frequentist, random-effects, network meta-analysis to calculate odds ratios ([ORs]; dichotomous outcomes) or standardised mean differences (continuous outcomes) with 95% CIs. The study protocol was registered with PROSPERO, CRD42020169951. Findings: We identified 28 395 studies through the database search and 334 from references of previous studies. We compared 11 family intervention models tested on a total of 90 randomised controlled trials with 10 340 participants (3579 females and 5632 males with sex indicated; median age 31 years [range 14–65]) in the network meta-analysis. Ethnicity data were not available. All interventions, with the exception of crisis-oriented interventions and family psychoeducation with two sessions or fewer, reduced the relapse rate significantly when compared with treatment as usual at the primary timepoint of 12 months. ORs compared with treatment as usual ranged from 0·18 (95% CI 0·12–0·27) for family psychoeducation alone to 0·63 (0·42–0·94) for community-based interventions involving family members. The results were robust in various sensitivity and subgroup analyses. The confidence in the estimates ranged from moderate to very low for different comparisons. Interpretation: Almost all family intervention models were efficacious in preventing relapse in schizophrenia. Family psychoeducation alone, without behavioural or skills training, was superior to the more complex models. Our results suggest that in contexts where there are financial constraints, family psychoeducation alone should be implemented. Funding: German Ministry for Education and Research.